KEYWORD AND COLLOCATION ANALYSIS IN PUBLIC POLICY DISCOURSE: A CASE STUDY OF PRESIDENT PRABOWO SUBIANTO’S SPEECH AT THE WORLD ECONOMIC FORUM 2026 - Mirsa Umiyati (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research analyzes keywords and collocation patterns in public policy discourse through a case study of President Prabowo Subianto's speech at the World Economic Forum (WEF) 2026. Using a corpus linguistics approach, this study identifies prominent keywords and collocation patterns that form the ideological construction of Indonesian government policies. The research data consists of the president's speech transcript delivered in Davos, Switzerland on January 22, 2026. Analysis was conducted through word frequency identification, keyness calculation, and collocation pattern analysis using a qualitative-quantitative approach. The research findings indicate that dominant keywords include "Indonesia," "peace," "stability," "growth," and "economy," which form three main themes: (1) the narrative of peace and stability as economic prerequisites, (2) the construction of credibility and state governance, and (3) the rhetoric of social justice and anti-corruption. The identified collocation patterns reveal discursive strategies that combine economic nationalism narratives with commitments to global governance. These findings contribute to understanding how state leaders construct policy legitimacy through lexical choices and linguistic patterns in international forums